Perceptions of the causes of The Troubles in Northern Ireland - Dillon, Michelle (Economic & Social Studies, 1990)
This paper uses data collected in the Irish Mobility Study (1973) to explore intra-Catholic patterns of differentiation, and differences in the attitudes of Catholics and Protestants, towards the causes of The Troubles. It also documents different perceptions of the national identity of people living in the North. On the basis of these findings, the paper notes the added complexity involved in understanding the Northern Ireland problem when the unit of analysis is extended to include the whole island. It suggests that using a Gramscian approach, as has been proposed by Fulton (1988), who argues that the conflict should be conceptualised in terms of an all-Ireland Catholic-nationalist bloc in opposition to a Protestant-loyalist bloc, is not as straightforward as it appears. The paper also suggests that any analysis of Ireland needs to be sensitive to the importance of jurisdictional location in culturally differentiating the Catholic population.
Keywords: The Troubles; Northern Ireland; perception; national identity; religion